2019
DOI: 10.1080/13880209.2019.1626448
|View full text |Cite
|
Sign up to set email alerts
|

Effects of puerarin on the pharmacokinetics of triptolide in rats

Abstract: Context: Puerarin and triptolide are sometimes used together for the treatment of disease in Chinese clinics; however, the drug-drug interaction between puerarin and triptolide is still unknown. Objective: This study investigates the effects of puerarin on the pharmacokinetics of triptolide in rats and clarifies its main mechanism. Materials and methods: The pharmacokinetic profiles of oral administration of triptolide (1 mg/kg) in Sprague-Dawley rats with (test group, n ¼ 6) or without pretreatment (control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Drug metabolizing reaction was reported in the PUE treated rats. It was shown that PUE inhibits the activity of P-gp or CYP3A4 [43]. P-gp is an ATP-dependent transmembrane efflux pump that is expressed in columnar epithelial cells of the lower gastrointestinal tract and canalicular surface of hepatocytes [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug metabolizing reaction was reported in the PUE treated rats. It was shown that PUE inhibits the activity of P-gp or CYP3A4 [43]. P-gp is an ATP-dependent transmembrane efflux pump that is expressed in columnar epithelial cells of the lower gastrointestinal tract and canalicular surface of hepatocytes [44].…”
Section: Discussionmentioning
confidence: 99%
“…Since the intestinal bioavailability (FI=F/[FH*Fa]) in female cynomolgus monkeys is very low (about 0.012 or 1.2 %), this suggests that the intestine plays a major role in the metabolism of PUE. The plausible enzymes in intestinal enterocytes metabolizing the PUE are P-gp and CYP3A [43]. PUE was reported as a plausible substrate of P-gp [47].…”
Section: Percent Recovery Pue-ivmentioning
confidence: 99%
“…The test group was pre-treated with puerarin at a dose of 100 mg/kg/day (dissolved directly in normal saline containing 0.5% methylcellulose at a concentration of 2 mg/mL) for 7 days before the administration of AS-IV. Next, AS-IV was orally administered to rats by gavage at a dose of 20 mg/kg (Du et al 2005;Wang et al 2019). Blood samples (250 lL) were collected into heparinized tubes via the oculi chorioideae vein at 0.083, 0.33, 0.5, 1, 2, 4, 6, 8, 10, 12 and 24 h after the oral administration of puerarin.…”
Section: In Vivo Pharmacokinetic Studymentioning
confidence: 99%
“…On the contrary, puerarin could affect the pharmacokinetics of some active compounds which were substrates of P-gp, MRP and CYP 450. Puerarin could significantly change the pharmacokinetic profiles of triptolide in rats probably though inhibiting the activity of P-gp or CYP3A4 (Wang et al., 2019). CYP3A4 enzyme was also involved in the metabolism of ivabradine, the AUC and C max of ivabradine in rats that were pretreated with puerarin were significantly higher than that of the ivabradine control group (Zhang et al., 2016).…”
Section: Pharmacokinetics Of Puerarinmentioning
confidence: 99%